2018
DOI: 10.1080/1070289x.2018.1486091
|View full text |Cite
|
Sign up to set email alerts
|

Constructions of Europe in the run-up to the EU referendum in the UK

Abstract: Andreouli, Eleni (2019). Constructions of Europe in the run-up to the EU referendum in the UK. Identities: global studies in culture and power, 26(2) pp. 241-259. For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In other work (Andreouli, ) we have shown that a narrative of ‘cosmopolitan Brexit’ also featured in the discourse of Leave supporters where Remain was positioned as elitist and Eurocentric and Brexit as open to the world beyond Europe. The latter is often presented as more authentically cosmopolitan and ethnically inclusive because it values migrants on the basis of their individual merits, rather than their status as Europeans.…”
Section: Three Axes For Exploring the Emergent Politics Of Brexitmentioning
confidence: 61%
See 2 more Smart Citations
“…In other work (Andreouli, ) we have shown that a narrative of ‘cosmopolitan Brexit’ also featured in the discourse of Leave supporters where Remain was positioned as elitist and Eurocentric and Brexit as open to the world beyond Europe. The latter is often presented as more authentically cosmopolitan and ethnically inclusive because it values migrants on the basis of their individual merits, rather than their status as Europeans.…”
Section: Three Axes For Exploring the Emergent Politics Of Brexitmentioning
confidence: 61%
“…In line with analyses of vote demographics (e.g., Goodwin & Heath, ), all were strong Remain supporters. This is clear from the beginning of the focus group, when the participants described continental Europe as more cosmopolitan and sophisticated than Britain (see also Andreouli, ). As put by one of the participants, Amanda,
… to me there is an impression of cool Europe, cool continental Europe, and British to me can sometimes equate to like, I think, maybe back a generation or two, how we might have to sit at a table with proper crockery... and make sure we use our proper things.
…”
Section: Three Axes For Exploring the Emergent Politics Of Brexitmentioning
confidence: 90%
See 1 more Smart Citation
“…Andreouli, Kaposi, & Stenner, ) in Extract 6 to mean the exact opposite of what it commonly refers to, particularly in Remain‐supporting accounts: from being associated with Eurosceptic and anti‐immigration attitudes, prejudice is here associated with Eurocentrism. This line of reasoning has been common among some Brexit supporters and can be seen in a broader narrative of “cosmopolitan Brexit” and “global Britain” (Andreouli, ) that gained prominence following the referendum. As has also been shown in analyses of skills‐based arguments on immigration (that migrants should be assessed on the basis of their skills, not their nationality), the notion of meritocracy works to discursively individualise migration and deracialise the exclusion of migrants (Gibson & Booth, ).…”
Section: Discussionmentioning
confidence: 88%
“…For example, immigration could be discussed in terms of Britain being able to control its own borders as a sovereign nation (political aspect), in terms of its impact on the U.K. economy (economic aspect), and/or in terms of its impact on Britain’s culture. The theme of culture was less prominent in the data compared to politics and the economy, and it is not explored in this article (see Andreouli, in press, for a discussion of this theme).…”
Section: Methodsmentioning
confidence: 99%